2012
DOI: 10.3389/fphys.2012.00283
|View full text |Cite
|
Sign up to set email alerts
|

Integration of peroxisomes into an endomembrane system that governs cellular aging

Abstract: The peroxisome is an organelle that has long been known for its essential roles in oxidation of fatty acids, maintenance of reactive oxygen species (ROS) homeostasis and anaplerotic replenishment of tricarboxylic acid (TCA) cycle intermediates destined for mitochondria. Growing evidence supports the view that these peroxisome-confined metabolic processes play an essential role in defining the replicative and chronological age of a eukaryotic cell. Much progress has recently been made in defining molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
87
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(88 citation statements)
references
References 129 publications
(188 reference statements)
0
87
0
Order By: Relevance
“…These cellular processes include the following: (1) glycogen degradation; (2) the glycolytic pathway; (3) the pentose phosphate pathway; (4) pyruvate conversion to acetyl-CoA; (5) the maintenance of redox balance between NAD and NADH with the help of carnitine and glycerol-3-phosphate shuttles; (6) ROS detoxification; (7) stress response; (8) glutathione synthesis; (9) gluconeogenesis; (10) ethanol formation; (11) the synthesis and hydrolytic degradation of triacylglycerols (TAG) and ergosteryl esters (EE), the 2 major neutral lipids; (12) the synthesis of various amino acids; (13) nucleotide synthesis; (14) the assembly of the 40S and 60S ribosomal subunits from numerous protein components whose levels were altered by LCA; and (15) proteasomal and vacuolar protein degradation. 4,5,39,41,38,71,72 We then subjected cellular proteins whose levels were changed in yeast grown in a medium supplemented with LCA to bioinformatic analysis with the help of the SPELL online search engine, 51 as described above for mitochondrial proteins. Just as our bioinformatic analysis of mitochondrial proteins revealed (see above), we found that each of the cellular proteins whose level was altered in yeast cultured with LCA belongs to the following 2 multi-clustered regulons: (1) the PMD regulon, which consisted of the rho 0 (Rtg2p governed) cluster, S1 cluster, general TCA cycle dysfunction cluster, kgd1D, kgd2D or lpd1D cluster, yme1Dmdl1D Figure 2.…”
Section: Lca Elicits Age-related Changes In Mitochondrial Proteomementioning
confidence: 99%
“…These cellular processes include the following: (1) glycogen degradation; (2) the glycolytic pathway; (3) the pentose phosphate pathway; (4) pyruvate conversion to acetyl-CoA; (5) the maintenance of redox balance between NAD and NADH with the help of carnitine and glycerol-3-phosphate shuttles; (6) ROS detoxification; (7) stress response; (8) glutathione synthesis; (9) gluconeogenesis; (10) ethanol formation; (11) the synthesis and hydrolytic degradation of triacylglycerols (TAG) and ergosteryl esters (EE), the 2 major neutral lipids; (12) the synthesis of various amino acids; (13) nucleotide synthesis; (14) the assembly of the 40S and 60S ribosomal subunits from numerous protein components whose levels were altered by LCA; and (15) proteasomal and vacuolar protein degradation. 4,5,39,41,38,71,72 We then subjected cellular proteins whose levels were changed in yeast grown in a medium supplemented with LCA to bioinformatic analysis with the help of the SPELL online search engine, 51 as described above for mitochondrial proteins. Just as our bioinformatic analysis of mitochondrial proteins revealed (see above), we found that each of the cellular proteins whose level was altered in yeast cultured with LCA belongs to the following 2 multi-clustered regulons: (1) the PMD regulon, which consisted of the rho 0 (Rtg2p governed) cluster, S1 cluster, general TCA cycle dysfunction cluster, kgd1D, kgd2D or lpd1D cluster, yme1Dmdl1D Figure 2.…”
Section: Lca Elicits Age-related Changes In Mitochondrial Proteomementioning
confidence: 99%
“…It is not surprising therefore that malfunction of peroxisomes leads to peroxisome-specific diseases (Braverman et al, 2013;Weller et al, 2003) and contributes to the pathology of Alzheimer's and Parkinson's diseases, aging, cancer, type 2 diabetes and heart failure (Beach et al, 2012;Colasante et al, 2015;Fransen et al, 2013;Islinger et al, 2012;Trompier et al, 2014). A useful distinction divides peroxisomal diseases into two groups: those in which single enzymatic functions are defective, and those where peroxisome biogenesis is defective per se.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relatively short and easily monitored replicative and chronological life spans of this genetically and biochemically manipulable unicellular eukaryote with annotated genome, it has been successfully used to (1) identify numerous novel longevity genes, many of which have been later implicated in regulating longevity of multicellular eukaryotic organisms; (2) establish the chemical nature of molecular damage that causes cellular and organismal aging and accelerates the onset of age-related diseases; and (3) identify a number of longevity-extending small molecules, many of which have been later shown to slow down aging, improve health, attenuate age-related pathologies and delay the onset of age-related diseases in multicellular eukaryotes [3,5,8,9,[18][19][20][21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%